The direct synthesis of hydrogen peroxide from H2 and O2 using Pd-Ga and Pd-In catalysts - Wang, Sheng; Lewis, Richard J.; Doronkin, Dmitry E.; Morgan, David J.; Grunwaldt, Jan-Dierk; Hutchings, Graham J.; Behrens, Silke (Catalysis science & technology, 2020)
The direct synthesis of hydrogen peroxide is investigated using PdGa/TiO2 and PdIn/TiO2 catalysts prepared by an acid-washed sol-immobilisation procedure, which allows for good control of particle size. The introduction of both Ga and In into a supported Pd catalyst leads to significantly reduced rates of H2O2 degradation in comparison to the monometallic counterpart. Detailed characterisation reveals that this enhancement is a result of selectively tuning the ratio of Pd oxidation states.